Early changes in extracellular matrix in Alzheimer's disease - François-Xavier Lepelletier; David Mann; Andrew Robinson; Emmanuel Pinteaux; Hervé Boutin (2015)
Although changes in extracellular matrix (ECM) scaffold have been reported previously in Alzheimer's disease (AD) compared to normal ageing, it is not known how alterations in the numerous components of the perivascular ECM might occur at different stages of AD. This study therefore investigates potential changes in basement membrane-associated ECM molecules in relation to increasing Braak stages.Thirty patients were divided into three groups (control subject, subclinical AD and AD patients). ECM levels of collagen IV, perlecan and fibronectin as well as human platelet endothelial cell adhesion molecule (hPECAM) were quantified by immunohistochemistry. Von Willebrand factor staining was measured to assess vessel density. Expression levels were correlated with the presence of amyloid plaques.Collagen IV, perlecan and fibronectin expression was increased in subclinical AD and AD patients when compared to controls, in frontal and temporal cortex, whilst no further increase was detected between subclinical AD and AD. These changes were not associated with an increase in vessel density, which was instead decreased in the temporal cortex of AD patients. In contrast, hPECAM levels remained unchanged. Finally, we found similar pattern in levels of amyloid deposition between the different Braak stages and showed that changes in ECM components correlated with amyloid deposition.Present data support the hypothesis that significant ECM changes occur during the early stages of AD. ECM changes affecting brain microvascular functions could therefore drive disease progression and provide potential new early investigational biomarkers in AD.